2020
DOI: 10.11648/j.ajtab.20200603.12
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Market Anomalies on the Inefficiency of Stock Returns

Abstract: This paper serves the purpose to analyses market anomalies and their agents on returns in the Iranian indexes between 2017 and 2020. Principled patterns in financial market are incompatible to the efficient market hypothesis, as stock market returns can be done applying these systematic models. Real investors may not be able to achieve the return and profitability due to the scarcity of their financial resources. Accordingly, the study of the role of real investors in the volatility of stock returns is very im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In fact, the efficient markets theory has little impact on the time cycle theory and our 24-solar-term method. There is also a study that shows the nonuniversality of the efficient markets theory and found cases to contradict it [24].…”
Section: Adaptive Market Hypothesis and Imperfection Of Efficient-market Hypothesismentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, the efficient markets theory has little impact on the time cycle theory and our 24-solar-term method. There is also a study that shows the nonuniversality of the efficient markets theory and found cases to contradict it [24].…”
Section: Adaptive Market Hypothesis and Imperfection Of Efficient-market Hypothesismentioning
confidence: 99%
“…Eight of the Chinese 24 solar terms are very prominent, namely, Chunfen (6), Xiazhi (12), Qiufen (18) and Dongzhi (24), which represent the most vigorous timepoints in each season and are the most important four solar terms; the other four are Lichun (3), Lixia (9), Liqiu (15) and Lidong (21). These four represent the beginning of each season and are the second important four solar terms.…”
Section: Grouping Of Solar Termsmentioning
confidence: 99%
See 2 more Smart Citations